Re-Engineering Public Libraries of Varanasi - Kumar Singh, Manendra; Tripathi, Aditya (Journal of Information and Knowledge, 2018)
The public library has a social mission; to provide various types of information, documents, books and e-services to fulfill information needs of its users. It exists to serve different communities. It works as a local gateway of knowledge which provides a basic condition for lifelong learning, independent decision-making and cultural development of the individual and various social groups. The government of India currently working on a smart city mission to enhances Indian cities1. The government of India has signed MOU with Japan to implement Kyoto city module for the development of Varanasi2. Public library services component appears to be missing in the smart city plan. In this study, 14 libraries were personally visited and data collected. Most of the public libraries are based on conventional services module which are inadequate in the current changing environment. Public library services need to be reengineered and some of the areas which need to be considered for this purpose are identified.